2020
DOI: 10.2147/dmso.s241998
|View full text |Cite
|
Sign up to set email alerts
|

<p>Protective Effect of Benzoquinone Isolated from the Roots of <em>Averrhoa carambola</em> L. on Streptozotocin-Induced Diabetic Mice by Inhibiting the TLR4/NF-κB Signaling Pathway</p>

Abstract: Background: Studies have demonstrated that the roots of Averrhoa carambola L. (Oxalidaceae), a traditional Chinese medicine, can be used to treat diabetes and diabetesrelated diseases. Nevertheless, the potential beneficial effects and mechanism of benzoquinone isolated from the roots of Averrhoa carambola L. (BACR) on diabetes remain unclear. Methods: Diabetic Kunming mice were injected with STZ (120 mgkg −1) in the tail vein. Fasting blood glucose (FBG) and the change of body weight were measured after oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…The hypoglycemic activity of benzoquinone isolated from the roots of A carambola on streptozotocininduced diabetic mice was evalualed. After 21 days of treatment, a dose of 120 mg/kg of benzoquinone showed the same therapeutic effect as metformin (300 mg/kg) reducing the blood glucose levels compared with the model control group (Qin et al, 2020).…”
Section: Averrhoa Carambolamentioning
confidence: 84%
“…The hypoglycemic activity of benzoquinone isolated from the roots of A carambola on streptozotocininduced diabetic mice was evalualed. After 21 days of treatment, a dose of 120 mg/kg of benzoquinone showed the same therapeutic effect as metformin (300 mg/kg) reducing the blood glucose levels compared with the model control group (Qin et al, 2020).…”
Section: Averrhoa Carambolamentioning
confidence: 84%
“…Interestingly, in contrast to DC group, there were no statistical differences of serum HDL-c levels in NC, MET, SVP-L, and SVP-H groups, which is consistent with a previous study ( 34 ). In short, it was indicated that SVP could prevent T2DM-induced hyperlipidemia, thereby reducing the risk of diabetic complications ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…There was a decline in blood glucose, serum creatinine, and blood urea nitrogen levels and an increase in the quantity and density of podocytes (Lu et al., 2019). In another study from 2020, the administration of benzoquinone isolated from the roots of Averrhoa carambola to male Kunming mice with induced diabetes found a reduction in the blood glucose levels when compared with a control group (Qin et al., 2020). Zhang et al showed that the beneficial effects of Averrhoa carambola extracts in mice with induced diabetes were probably due to inhibition of the TLR4/TGF‐β signaling pathway by active compounds like DMDD (Zhang et al., 2020).…”
Section: Results and Discussion Of Trendsmentioning
confidence: 99%